Seasonal physical performance of a professional team`s football players in a national league and European matches - Smpokos, E.; Mourikis, C.; Linardakis, M. (Journal of Human Sport & Exercise, 2018)
To quantify the seasonal motor skills profile by a professional team`s football players in official matches covered all pre-season matches in national and European championships of the 2016/2017 season. Twenty-seven players were sampled using Global-Positioning-System Technology (GPS). Total distance in meters-(TD), Maximal-Sprinting-Speed running (MS), Very-High-Intensity speed running (VHS), relative Distance/time (D/T) were estimated at two high speed categories: VHS; from 19.8 to 25.2Km/h and MS;>25.2Km/h). Analysis of variance was performed. Midfielders players seem to cover significantly greater mean TD than defenders and forwards (10363 vs. 9887 and 9717 meters, respectively, p<0.001). Furthermore, Midfield players covered greater mean D/T than forward group (99.3 vs. 92.0 meters/mins, respectively, p=0.001). With regard to the match outcome, lower average of TD was covered in matches were the end result was the defeat than those with match outcome win or draw (9488 vs. 10188 and 10148 meters, respectively, p<0.001). Similarly, the same was noted when the TD levels were controlled for the match outcome, with adjustment of the characteristics of the players, playing position and the three periods of the competitive season. This study showed the changes in all types of tested motor skills by the top national team across an annual season. The use of this monitoring approach may contribute to the development of individual training programs for the football players according to their position and specific demands through the season which serve to further enhance soccer performance and reduce the incidence of fatigue or injury.